229k views
3 votes
50 point for this question:

Find values of a and b that make the following equality into identity:

50 point for this question: Find values of a and b that make the following equality-example-1
50 point for this question: Find values of a and b that make the following equality-example-1
50 point for this question: Find values of a and b that make the following equality-example-2
User Foufrix
by
5.3k points

1 Answer

4 votes

Answer:

1) The values of 'a' and 'b' are
$ (3)/(4) $ and
$ (3)/(4) $ respectively.

2) The values of 'a' and 'b' are '3' and '-3' respectively.

Explanation:

1) Given:
$ (3x)/((x - 2)(3x + 2)) = (a)/(x - 2) + (b)/(3x + 2) $

We solve this by partial fraction method.

Taking LCM in the RHS we get,


$ (3x)/((x - 2)(3x + 2)) = (a(3x + 2) + b(x - 2))/((x - 2)(3x + 2)) $


$ \implies 3x = a(3x + 2) + b(x - 2) $

To find the value of 'a', substitute x = 2. This would make 'b' vanish leaving an equation with 'a'.


$ \therefore 3(2) = a(3.2 + 2) + b (2 - 2) \implies 6 = a(8) $


$ \implies a = (-2)/(3) $

Now, Substitute
$ x = (-2)/(3) $ to solve for 'b'.


$ \implies 3((-2)/(3)) = a (3.(-2)/(3) + 2) + b((-2)/(3) -2) $


$ \implies -2 = b (-8)/(3) $


$ \implies b = (3)/(4) $

Therefore, a =
$ (3)/(4) $ and b =
$ (3)/(4) $

2) Given
$ (3)/(x^2 - 5x + 6) = (a)/(x - 2) + (b)/(x - 3) $

We follow the same procedure as (1).

Taking LCM we get


$ (3)/(x^2 - 5x + 6) = (a (x - 3) + b(x - 2))/((x^2 - 5x + 6)) $


$ \implies 3 = a(x - 3) + b(x - 2) $

Substituting x = 2, we get:

3 = a(-1)
$ \implies a = -3 $

Also, Substituting x = 3, we get:

3 = b(1)


$ \implies b = 1 $

Therefore, the values of a and b are -1 and 1 respectively.

User Alex McKenzie
by
5.7k points